Breaking gender stereotypes: The relationships between psychological gender, personality and the system of values in the case of the female field hockey players - Basiaga-Pasternak, J.; Wojtowicz, A.; Kosiba, G.; Bogacz-Walancik, A. (Journal of Kinesiology and Exercise Sciences, 2017)
The aim of the study was to determine the predictors of female sports success by examining the relations between psychological gender on the one side and personality and the system of values on the other in the case of female field hockey players. An attempt was made to demonstrate what the dominant psychological gender of the athletes under the study was, while it had been assumed that it would be the androgynic type. The research was conducted among field hockey Polish National Team. The average age was 21,42. The present research did not confirm the dominance of masculine or androgynic types among the female field hockey players under study. A personality type, therefore, was related to the system of values, and a psychological gender was a factor moderating the preferred values. In the case of androgynic types under study, the dimension Openness was connected with the decrease of the importance of a True Frendship and Agreeableness with the increase in the Forgiveness value. Androgynic athletes were more oriented on terminal personal values, while feminine ones were oriented on social goals. Feminine athletes were characterized by lower level of extraversion than androgynic and undifferentiated subjects.